2020
DOI: 10.1016/j.ejpn.2020.10.006
|View full text |Cite
|
Sign up to set email alerts
|

E.U. paediatric MOG consortium consensus: Part 1 – Classification of clinical phenotypes of paediatric myelin oligodendrocyte glycoprotein antibody-associated disorders

Abstract: Over the past few years, increasing interest in the role of autoantibodies against myelin oligodendrocyte glycoprotein (MOG-abs) as a new candidate biomarker in demyelinating central nervous system diseases has arisen. MOG-abs have now consistently been identified in a variety of demyelinating syndromes, with a predominance in paediatric patients. The clinical spectrum of these MOG-ab-associated disorders (MOGAD) is still expanding and differs between paediatric and adult patients. This first part of the Paedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
129
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 104 publications
(137 citation statements)
references
References 124 publications
(213 reference statements)
4
129
2
2
Order By: Relevance
“…More specific for paediatric MOGAD is the phenotypical diversity, and its correlation to outcome needs to be addressed. In addition to the frequent MOGAD clinical presentations of acute disseminated encephalomyelitis (ADEM), optic neuritis (ON) and transverse myelitis (TM), also other less typical and rare presentations such as MOG-ab-positive encephalitis-like and leukodystrophy-like phenotypes, and non-classifiable syndromes are seen [5]. Additionally, prevalence of these diverse phenotypes differs according to age: Clinical events in patients nine years or younger have been shown to be more likely to affect the brain, whereas in patients older than nine years clinical events are more likely to affect the optic nerve [11].…”
Section: Key Elements Of Outcome Assessment In Paediatric Mogadmentioning
confidence: 99%
See 2 more Smart Citations
“…More specific for paediatric MOGAD is the phenotypical diversity, and its correlation to outcome needs to be addressed. In addition to the frequent MOGAD clinical presentations of acute disseminated encephalomyelitis (ADEM), optic neuritis (ON) and transverse myelitis (TM), also other less typical and rare presentations such as MOG-ab-positive encephalitis-like and leukodystrophy-like phenotypes, and non-classifiable syndromes are seen [5]. Additionally, prevalence of these diverse phenotypes differs according to age: Clinical events in patients nine years or younger have been shown to be more likely to affect the brain, whereas in patients older than nine years clinical events are more likely to affect the optic nerve [11].…”
Section: Key Elements Of Outcome Assessment In Paediatric Mogadmentioning
confidence: 99%
“…Regarding functional outcome, the MOGAD phenotype will likely determine the most affected domains; cognition in patients with ADEM phenotype, bladder and motor problems with TM phenotype, visual problems with ON phenotype and epilepsy with encephalitis-like phenotype. As the functional outcome will be highly dependent on the clinical phenotype, in future studies a standardised classification, as suggested in this special issue Part 1 [5], will be of importance in order to correctly predict outcome.…”
Section: Key Elements Of Outcome Assessment In Paediatric Mogadmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several paediatric monophasic and multiphasic immune-mediated acquired demyelinating syndromes (ADS) like acute disseminated encephalomyelitis, optic neuritis and transverse myelitis have been shown to be associated with the presence of antibodies targeting myelin oligodendrocyte glycoprotein (MOGab), a small yet important component of the myelin sheet [1]. As these MOG-ab-associated disorders (MOGAD) are rare and clinically diverse there is a need for consensus on both the clinical classification and management of these children, that is currently lacking.…”
mentioning
confidence: 99%
“…Part 1 reviews the clinical features of the different monophasic and multiphasic clinical subtypes of paediatric MOGAD and introduces a clinical classification of MOGAD [1]. In part 2 the radiological features of these entities are delineated in addition to an overview of the differences between of the radiological features of paediatric MOGAD and other ADS like multiple sclerosis and aquaporin-4 mediated diseases [2].…”
mentioning
confidence: 99%